2003
DOI: 10.1354/vp.40-3-317
|View full text |Cite
|
Sign up to set email alerts
|

Narthecium ossifragum(L.) Huds. Causes Kidney Damage in Goats: Morphologic and Functional Effects

Abstract: Abstract. We studied the effects of Narthecium ossifragum on goat kidneys. Twenty-five Norwegian dairy goats, 5 weeks to 4 months of age, were orally dosed with an aqueous extract from N. ossifragum. In experiment 1, we studied microscopic and functional changes in 12 animals that were euthanatized 2, 3, 4, 5, and 6 days after treatment. In experiment 2, we included ultrastructural studies on serial renal biopsies and urine analysis from five extract-treated animals and two controls. In addition, urine samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 26 publications
2
4
0
1
Order By: Relevance
“…This sonographic finding was identified in 14% of patients with renal dysfunction over a 1 year period. A similar sonographic finding of perirenal fluid in renal failure has been recognized in the goat in nephrotoxicity caused by Narthecium ossifragum , 11 a perennial herb of the lily family, and in ethylene glycol toxicity and leptospirosis in the dog but it has not been reported in more recently described nephrotoxicoses caused by several lily species in the cat 12 or raisins and grapes in the dog 13 or with other causes of acute renal failure. Herein we describe the sonographic features and underlying causes of perirenal effusion in dogs and cats with acute renal failure and discusses the potential pathophysiologic mechanisms responsible for the accumulation of such effusions.…”
Section: Introductionsupporting
confidence: 68%
“…This sonographic finding was identified in 14% of patients with renal dysfunction over a 1 year period. A similar sonographic finding of perirenal fluid in renal failure has been recognized in the goat in nephrotoxicity caused by Narthecium ossifragum , 11 a perennial herb of the lily family, and in ethylene glycol toxicity and leptospirosis in the dog but it has not been reported in more recently described nephrotoxicoses caused by several lily species in the cat 12 or raisins and grapes in the dog 13 or with other causes of acute renal failure. Herein we describe the sonographic features and underlying causes of perirenal effusion in dogs and cats with acute renal failure and discusses the potential pathophysiologic mechanisms responsible for the accumulation of such effusions.…”
Section: Introductionsupporting
confidence: 68%
“…While the low levels of PUN recorded in this experiment agrees with the finding of Reed et al, (1990) who reported that high levels of tannins in the diets affect the level of PUN in the blood negatively; the levels of Cr recorded in this experiment may be described as good, this agrees with the finding of Wisloff et al, (2003), they reported that high levels of Cr in the blood may be caused by poor filtration in the kidneys due to muscle catabolism when the kidneys are either weak or diseased.…”
Section: Resultssupporting
confidence: 93%
“…Bog asphodel toxicity has been described in several countries in numerous ruminant species, including moose, cattle, red deer, sheep, goats and reindeer in Norway (Flåøyen and others 1995a, b, c, 1999, Vikøren and others 1999, Wilsløff and others 2003) and cattle in Ireland (Malone and others 1992). The active toxic component has been identified as 3-methoxy-2(5H)-furanone (Langseth and others 1999).…”
mentioning
confidence: 99%